Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
B) by first reversing Reaction 2 and then adding the enthalpy of Reaction 1 and the enthalpy of Reaction 2
Explanation:
C2H2 (g)+2H2 (g)→C2H6 (g) ΔH=−75 kcal
C2H4 (g)+H2 (g)→C2H6 (g) ΔH=−33 kcal
C2H2 (g)+H2 (g)→C2H4 (g) ΔH= ?
First step - Reverse reaction 2.
C2H6 (g) → C2H4 (g) + H2 (g) ΔH= 33 kcal
Second step - Add reaction 1 and the reversed reaction 2. This gives us:
C2H2 (g) + 2H2 (g) + C2H6 (g) → C2H6 (g) + C2H4 (g) + H2 (g)
Simplifying gives:
C2H2 (g)+H2 (g)→C2H4 (g)
The correct option is:
B) by first reversing Reaction 2 and then adding the enthalpy of Reaction 1 and the enthalpy of Reaction 2
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.